PEMANFAATAN POS PEMBINAAN TERPADU (POSBINDU) OLEH WANITA LANSIA DALAM RANGKA MENCEGAH PENYAKIT TIDAK MENULAR DI DESA AMBARAWA TIMUR (LP3K Lampung, 2022)
The Non-Communicable Disease Integrated Guidance Post is the community's participation in conducting early detection and monitoring of PTM risk factors which are carried out in an integrated, routine, and periodic manner. The main targets of the PTM Posbindu program are healthy, risky community groups and people with PTM aged 15 years and over. The purpose of this study was to describe the use of guidance posts by elderly women in order to prevent non-communicable diseases in the village of East Ambarawa. The result of this activity is that the community is greatly helped and facilitated in terms of knowledge about health.